PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) BERBANTUAN MEDIA WIZER.ME PADA MATERI TEKS DRAMA SISWA KELAS XI - Anggi Rahmawati; Diah Eka Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the procedure for the development, form, and feasibility of E-LKPD Assisted by Media Wizer.me on Drama Text Materials for Grade XI Students. This research uses the Research and Development (R&D) method by applying the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research stage begins with the analysis of needs and problems, media design design, product development in Wizer.me media platforms, limited implementation, and final product evaluation. Product assessment is carried out by validators subject matter experts and media experts, and reinforced with assessments by teachers in the field of study. The results of the study show that: (1) media development is based on the need for students and teachers for interactive and technology-based digital teaching materials (E-LKPD) to support the Independent Curriculum; (2) E-LKPD is developed in the form of an electronic worksheet (non-print) that integrates multimedia and question items based on cognitive variation of Bloom's Taxonomy to the C6 domain (Create); (3) The results of the validation of the subject matter expert show an average score of 88.18% with the category